Pengaruh Modal Kerja, Likuiditas, Struktur Modal Terhadap Profitabilitas Perusahaan Manufaktur 2012 - 2014 - Emillia Sastra (Jurnal Ekonomi, 2019)
The purpose of this empirical research is to obtain empirical evidence about the influence of working capital, liquidity and capital structure on the profitability of manufacturing companies listed on the stock exchange from 2012-2014. This research used manufacturing companies for a total of 198 data in three years and that was selected using the purposive sampling method. The data used in this research are secondary data in the form of financial statements. The results showed that the working capital and liquidity has a positive significant effect on profitability, the capital structure does not have a significant effect on profitability. The testing showed independent variable has a significant impact on the profitability and show that the correlation of the independent variables has a strong relationship to the dependent variable. Testing results show that the coefficient of determination of 55.1%, the dependent variable is affected by the independent variable, while the remaining 44,9 % is explained by other variables.